SHORT TERM INTER-PREGNANCY INTERVAL AND MATERNAL OUTCOME - Zarmina Talpur1, Najma Bano Shaikh2, Sajida Yousfani3, Nabila Hassan4, Kiran Batool5, Anila Mahmood6., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
OBJECTIVE: To identify negative impact of short inter-pregnancy interval on maternal outcome in woman attending Liaquat University hospital Hyderabad. MATERIAL AND METHODS: The cross-sectional study was undertaken in pregnant females attending obstetrics and gynaecology department at Liaquat University Hyderabad, during Six months from Jun, 2019 to December 2019. All the women of pregnancy within 12 months of last baby born, age less than 40 years, multiparous, who breast feed their child and those who conceived naturally without any assisted reproductive technique were included. All the information was gathered via self-made study proforma. RESULTS: Total 116 patients were subjected; their mean age was 29.03+5.77 years. Amongst women who presented with short inter pregnancy, 81.9% were anemic. However, 44.8% woman had premature rupture of membrane and 25.0% woman had pre-eclampsia. Maternal complications were statistically insignificant according to maternal age and duration of pregnancy interval. CONCLUSION: The study concluded that there were adverse effects frequently observed in short interpregnancy interval in the pregnant woman attending in our setup. Thus, woman may be given awareness of it and a proper inter-pregnancy interval may be adopted.